2019
DOI: 10.1177/1179556519834524
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of OXA-48 Carbapenemase Producing Klebsiella pneumoniae in a Neonatal Intensive Care Unit in Marrakech, Morocco

Abstract: Goal:This work aims to describe and explore the circumstances of appearance of Klebsiella pneumoniae producing OXA-48 carbapenemase, which has occurred in a neonatal intensive care service at the Mohammed VI University Hospital of Marrakech.Results:During February 2015, the alert was triggered by the isolation of 6 isolates of K pneumoniae with the same antibiotic susceptibility profile in the neonatal intensive care service, suggesting a possible outbreak. Blood cultures represented the main site of isolation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Since the positive predictive value of OXA‐48 is 80·0%, it should be noted that MAST‐ Carba plus (disc E) contained temocillin, and K. pneumoniae may occasionally show temocillin resistance, leading to false‐positive OXA‐48 production (Zioga et al ; Mathers et al ). In addition, the sensitivity of KPC producers is only 82·3%, indicating that the sensitivity of MAST‐ Carba plus to predict KPC production needs to be further improved (Miao et al ; Taoufik et al ). However, limited to financial and material resources, the types of MBLs, KPC and OXA‐48 carbapenemase genes are limited, and the strains harbouring combined resistance mechanisms could not be detected by MAST‐ Carba plus .…”
Section: Resultsmentioning
confidence: 99%
“…Since the positive predictive value of OXA‐48 is 80·0%, it should be noted that MAST‐ Carba plus (disc E) contained temocillin, and K. pneumoniae may occasionally show temocillin resistance, leading to false‐positive OXA‐48 production (Zioga et al ; Mathers et al ). In addition, the sensitivity of KPC producers is only 82·3%, indicating that the sensitivity of MAST‐ Carba plus to predict KPC production needs to be further improved (Miao et al ; Taoufik et al ). However, limited to financial and material resources, the types of MBLs, KPC and OXA‐48 carbapenemase genes are limited, and the strains harbouring combined resistance mechanisms could not be detected by MAST‐ Carba plus .…”
Section: Resultsmentioning
confidence: 99%
“…OXA-48 is the most prevalent carbapenemase gene detected in Morocco, as is the case in the present work. After its initial identification from a K. pneumoniae isolates in Rabat in 2010, from a 60-year-old man with no previous medical history [ 24 ], OXA-48 producers have intensively become the most CRE responsible for nosocomial infections in our country [ 28 , 30 , 41 ]. Indeed, North African countries (mainly Egypt, Libya, Tunisia and Morocco) are considered the principal reservoirs of OXA-48 producing Enterobacteriaceae [ 21 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Morocco, the situation of carbapenem-resistant Enterobacteriaceae has been the subject of only a few and outdated studies [ 25 , 26 ]. Most current and available research is confined to case reports or research studies that have focused on few patient numbers, for specific hospital units, specific bacterial species and specific genes, over a short period of time [ 27 , 28 , 29 , 30 ]. Thus, we conducted this one-year surveillance study (2018) to characterize the dissemination and characteristics of carbapenem-resistant Enterobacteriaceae (including bla OXA-48, bla KPC, bla IMP, bla VIM, and bla NDM) among hospitalized patients, from different units, in Mohamed VI University Hospital, Marrakech, Morocco.…”
Section: Introductionmentioning
confidence: 99%
“…Carbapenem-resistant Enterobacteriaceae are an emerging problem, which spreads among our most vulnerable populations, children 26. Many carbapenem resistance genes, such as bla KPC-2 ,21 bla NDM-1 ,27 bla OXA-48 ,28 bla OXA-232 and bla IMP-38 ,29,30 have been found in K. pneumoniae outbreak strains in the newborn. Although NDM-1 enzyme was previously reported as the most prevalent type of carbapenemase in children,31 our current results suggested that the emergence of NDM-5-producing K. pneumoniae caused nosocomial outbreak in neonatal unit.…”
Section: Discussionmentioning
confidence: 99%